Características arquitectónicas del sitio arqueológico de Inkilltambo y su relación con el agua y la roca (Distrito de San Sebastián- Cusco) - Apaza Huamaní, Betshy (2019)
ABSTRACT In the Kallachaca ravine of the San Sebastian district of the department of Cusco is the Archaeological Site of Inkilltambo, a place with particular constructive characteristics that are part of an ideological aspect typical of pre-Hispanic times, to be more accurate of the late horizon. Inkilltambo as an archaeological site had very little research, and those that existed did not provide much information in context of what could be Inkilltambo, however, they got involved in particularities and individualized their conclusions in use and function by excavated site, which helps the interpretation of this research topic to know what position occupies Inkilltambo within the context that is located and what was the cause of its construction in relation to the natural elements that surrounds it ?. For this purpose, all the historical, ethnohistorical and archaeological antecedents were investigated that provided general references but not to detail as expected, the site was analyzed and architecturally searching for the constructive characteristics of the same and the relationship that the building has with the natural elements present, as the imposing rocky outcrops and the water resource that crosses the archaeological site, arriving at the conclusion that this archaeological site fulfills a ceremonial function, and for this they worked the rock of the medium finely, they built their planimetric arrangement around it, they associated it with the present water resource, and they came giving it the degree that corresponds to it with a change in the constructive process as an ornament, changing the rigors of primitive rustic walls for a fine padding. Then we can say that, Inkilltambo was a Waka cult of water where small enclosures were built as stores and / or workshops, the slopes were adapted as containment walls and agricultural platforms, channels of various functions were created, invested the river and a mirror of water was created for purely ceremonial purposes